Struktur Komunitas Dan Kelimpahan Fitoplankton Di Pulau Kapoposang Kabupaten Pangkajene Dan Kepulauan, Provinsi Sulawesi Selatan (Abundance and Species Assemblage of Phytoplankton at Kapoposang Island, Pangkajene and Kepulangan Regency, South Sulawesi Province) - Rukminasari, Nita (Program Studi Manajemen Sumber Daya Perairan, 2018)
This research was aim to compare community structure and abundance of phytoplankton in Kapoposang Island. The result of this research was expected to be used as an information of the effect of waters quality on abundances, community structure and phytoplankton species composition in Kapoposang Island. This research was conducted on February and May 2016 in Kapoposang Island, Pangkajene and Islands Regency. Identification of samples was conducted in Fish Pest and Diseases Laboratory, Department of Fisheries, Faculty of Marine Science and Fisheries, Hasanuddin University. The results showed community structure of phytoplankton in Kapoposang Island based on sampling station were not significantly different (P>0,05), whereas community structure of phytoplankton based on rainy and summer seasons were significantly different (p<0,05).Alexandrium kutneraee, Toxarium undulatum dan Bellerochea horologicalesis most contribute species in Kapoposang Island the most average abundancesof phytoplankton was foundon summer season in Kapoposang Island1.591.494 cells/L.Both of the islands has high equitability index value and the distribution was homogeneous. The value of diversity index showed in all of the stations, phytoplankton community were mid stable and the dominance index showed both of the islands have dominant species.Keywords: Kapoposang Island, Phytoplankton, community structure, abundance, ecological index